2019
DOI: 10.1111/cxo.12836
|View full text |Cite
|
Sign up to set email alerts
|

Structure versus function in high myopia using optical coherence tomography and automated perimetry

Abstract: The correlation between retinal layer thicknesses and visual field sensitivity could be explained by myopia-related losses due to lateral retinal stretching, with further research required to investigate this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…According to Moghadas et al, the decreased sensitivity of the VF examination in high myopia was related to the decrease in the thickness of the retinal layer. 58 Decrease in the thickness of the ganglion cell layer could be caused by stretching of the retina, and Wolsley et al explained that this reduction in thickness can be mainly divided into photoreceptor cells and the inner layer of the retina. 59 It is also confirmed that there is variation in macular thickness in patients with myopia, and such foveal depression and photoreceptor outer segment elongation may lead to decreased visual function.…”
Section: Discussionmentioning
confidence: 99%
“…According to Moghadas et al, the decreased sensitivity of the VF examination in high myopia was related to the decrease in the thickness of the retinal layer. 58 Decrease in the thickness of the ganglion cell layer could be caused by stretching of the retina, and Wolsley et al explained that this reduction in thickness can be mainly divided into photoreceptor cells and the inner layer of the retina. 59 It is also confirmed that there is variation in macular thickness in patients with myopia, and such foveal depression and photoreceptor outer segment elongation may lead to decreased visual function.…”
Section: Discussionmentioning
confidence: 99%
“…The wider temporal window in high myopia may be related to the changes in the retina. With the abnormal elongation of the globe, 4 high myopia is associated with a variety of anatomical changes in the retina, 10 , 44 46 which have been linked to retinal functional deficits, 5 , 9 , 44 , 47 50 such as the delayed mfERG responses 15 , 50 and decreased macular light sensitivity. 9 , 44 Park et al 46 reported that the photoreceptor layer thickness in the foveola significantly decreased with increasing myopia.…”
Section: Discussionmentioning
confidence: 99%
“…With the abnormal elongation of the globe, 4 high myopia is associated with a variety of anatomical changes in the retina, 10 , 44 46 which have been linked to retinal functional deficits, 5 , 9 , 44 , 47 50 such as the delayed mfERG responses 15 , 50 and decreased macular light sensitivity. 9 , 44 Park et al 46 reported that the photoreceptor layer thickness in the foveola significantly decreased with increasing myopia. Similarly, Wang et al 44 found that the thickness of the myoid and ellipsoid zone within 2° from the macular center was correlated with the axial length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High myopia is associated with significant long‐term risks of vision impairment, from pathologic conditions such as retinal detachment and glaucoma . Using OCT, Moghadas Sharif et al show that ganglion cell layer thinning may lead to visual field defects in highly myopic eyes, with these myopia‐related visual field losses possibly due to lateral retinal stretching.…”
mentioning
confidence: 99%